2022
DOI: 10.3390/biom12050617
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Intrinsically Disordered GPCR C-Terminal Region, Major Actor in Arrestin-GPCR Interaction

Abstract: Arrestin-dependent pathways are a central component of G protein-coupled receptor (GPCRs) signaling. However, the molecular processes regulating arrestin binding are to be further illuminated, in particular with regard to the structural impact of GPCR C-terminal disordered regions. Here, we used an integrated biophysical strategy to describe the basal conformations of the C-terminal domains of three class A GPCRs, the vasopressin V2 receptor (V2R), the growth hormone secretagogue or ghrelin receptor type 1a (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…2b), from residues 356 to 364 (called V2-1), suggesting an β-strand conformation in this region. Interestingly, we showed previously that V2-1 contained a helical conformation in the non-phosphorylated form (wt-V2R-Cter) (Guillien et al, 2022). This loss of helical content between the wt and the pm variant was also substantiated by the decrease of percentage of 3 JHNHA scalar coupling bellow 6 Hz (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…2b), from residues 356 to 364 (called V2-1), suggesting an β-strand conformation in this region. Interestingly, we showed previously that V2-1 contained a helical conformation in the non-phosphorylated form (wt-V2R-Cter) (Guillien et al, 2022). This loss of helical content between the wt and the pm variant was also substantiated by the decrease of percentage of 3 JHNHA scalar coupling bellow 6 Hz (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…A combined Size Exclusion Chromatography-Multi Angle Light Scattering (SEC-MALS), Circular Dichroism (CD) and Nuclear Magnetic Resonance (NMR) analysis showed that these pm variants are monomeric and disordered domains with transient secondary structures (Fig. 1), as is the case of their non-phosphorylated (wt-GPCR-Cter) forms (Guillien et al, 2022). Indeed, SEC-MALS profiles of pm variants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the unique isoforms and their IDRs (detected mainly in the 3 rd intracellular loop and the C-terminal tail) are typically enriched in tissue-specific isoforms, resulting in tissue-specific protein-protein interactions ( 90 ), including the GPCRs ( 97 ). Notably, the IDRs in the C-terminal of GPCRs are proposed to have a high potential for new target-binding partners ( 98 ). The importance of the N-terminal for the activation of two distinct GPCR isoforms was also highlighted ( 99 ).…”
Section: Function and Structural Considerations Of Protein Isoformsmentioning
confidence: 99%